Plan de mejoras a la gestión administrativa en la procesadora de yuca (Manihot eslenta Crantz "Luisan" del Sitio Bejuquillo, Canuto 2010 - Fernández Cevallos, Mariana Annabell (2011)
In the present investigation there are listed elements that will improve the administration, finance and production of “LUISAN” cassava processor, meeting the demands of the market in quality and volume. The first phase was the assessment of the process according to the Good Processing Practice analysis using the observation, interview and survey to help in the collection of necessary data allowing the understanding of the technology being used in the production and plant size. Having identified the problem we proceeded to implement the activities and process flows by a mass balance of the products determining the loss in the process and equipment capabilities. Microbiological and bromatological studies were performed on starch and fresh cassava in the laboratories of the ESPAM MFL, checking the status of raw material and final product. We determined the organizational and administrative system through a structural organization starting with the manager, secretary, accountant, production manager, employees and part-time employees. SWOT analysis was performed covering the strengths, weaknesses, opportunities and threats, making the company more competitive. Finally we determined the investment plan for the implementation of new technology. The economic profile is based on calculating the main parameters of the project evaluators such as: IRR 55%, NPV $209,159.78, Break Even analysis and Profitability that were 16.84% 29.57%, these calculations based on determining the assets, liabilities and working capital.